Evaluation of Slaughter Stress Responses in the Dromedary Camel - Abdelilah, Lemrhamed; Rabab, Tabite; Najia, El Abbadi; Mohammed, El Khasmi; Bernard, Faye (International Journal of Livestock Research, 2019)
Slaughter stress responses were evaluated in the dromedary camel by analyzing hematocrit (Hct), neutrophil/lymphocyte ratio (NLR), hemolysis (H%), catalase activity (CATa) and plasma levels of cortisol (COR), triiodothyronine (T3), thyroxine (T4), glucose and malondialdehyde (MDA). Blood was collected during three different steps: at the arrival of the animals at the slaughterhouse just after unloading (step 1), at the end of a rest period of 16 to 20 hours (step 2) and finally during bleeding (step 3) after exposure to traditional slaughter stress. NLR, H%, MDA, glucose, COR, T3 and T4 measured at step 2 were significantly (P<0.05) lower compared to those observed at step 1 or step 3. On the contrary, CATa measured at step 2 were significantly (P<0.05) higher than that analyzed at steps 1 and 3. In the camel, the slaughter procedure used here was much more stressful and was able to alter the physiology of the animal.